Detection of Listeria pathogens by gradient/constant denaturing gel electrophoresis - A. Al-Mariri; L. Ramadan; L. Al-Halab (Bulgarian Journal of Veterinary Medicine, 2018)
Listeriosis is a serious, but preventable disease, and the virulence factor of this disease is produced only by the two pathogenic species L. monocytogenes and L. ivanovii in humans and/or animals. In this study, we used both denaturing gradient gel electrophoresis (DGGE) and constant denaturing gel electrophoresis (CDGE) as molecular methods combined with Polymerase Chain Reaction (PCR) for the detection and identification of Listeria pathogens on 543 samples of raw milk collected from all Syrian provinces. The two methods are based on the PCR amplification of a fragment of the InlC gene (virulence gene) from the studied Listeria species and on the analysis of the PCR products ob-tained by DGGE/CDGE. Based on the differences present in the sequences amplified, it was possible to obtain species-specific DGGE/CDGE migration that allowed fast and easy identification of the virulence and pathogenicity of L. monocytogenes and L. ivanovii in humans and/or animals, in order to reduce the incidence of Listeria bacteria in the environment and foods and to prevent the occur-rence of listeriosis in animal and human hosts.